Perioperative safety assessment of patients undergoing unilateral or bilateral hip replacements - Zhou, Zhenzhong; Cai, Gaorui; Yuan, Shanyou; Song, Lixia; Qian, Ping; Wang, Xueming; Ning, Xianjia; Wang, Jinghua; Jiang, Wenxue (Frontiers in Surgery, 2023)
Introduction: Due to the aging of the world population and the increase of obesity rate, it is expected that the number of joint replacement surgery will continue to increase in the next few years. This study evaluated the safety differences between unilateral and bilateral hip replacement surgeries. Methods: The data for patients who underwent hip arthroplasty in 2021 and 2022 were examined. The data set included 68 patients who were grouped according to the type of hip replacement needed, sex, age, and body mass index. Total blood loss and operative time were the safety-related indicators used to compare the groups. Results: Regardless of whether the unilateral replacement group was compared with the overall bilateral replacement group or separately with the staged and simultaneous bilateral replacement groups, simultaneous bilateral replacement surgeries were equally safe as the other types of hip replacements. The total blood loss and operative time for the simultaneous bilateral replacement group were not significantly different from those in the unilateral and staged bilateral replacement groups. For overweight patients, the operative time for simultaneous bilateral replacements was significantly shorter than that for unilateral replacements. Conclusions: These findings suggest that for patients requiring bilateral hip replacements, the blood loss risk for patients undergoing simultaneous bilateral hip replacements was similar to that for patients undergoing either unilateral or staged bilateral hip replacements. Thus, simultaneous bilateral total hip replacement (THR) are safe and should be considered for candidate patients.